Indigenous eco-archaeology: past, present, and future of environmental stewardship in central coastal California - Apodaca, Alec; Sanchez, Gabriel M.; Sigona, Alexii; Grone, Michael; Lopez, Valentin; Lightfoot, Kent G. (Frontiers in Environmental Archaeology, 2024)
The Amah Mutsun Tribal Band (AMTB) has stewarded terrestrial and aquatic resources in central California since time immemorial. Successive waves of European and Euro-American colonization have sought to suppress and erode AMTB's relationship with land, stewardship, and natural resources. The Tribe has mobilized anthropological and historical ecological data that demonstrate the effect of long-term Indigenous stewardship through cultural burning and other resource stewardship strategies. These Indigenous landscape legacies have influenced ecosystem structure and the sustainability of culturally important species. This paper focuses on the process of bridging archaeological research with contemporary stewardship efforts related to protecting, preserving, and caring for Tribal cultural heritage that exists from a landscape perspective. The collaborative research has helped clarify the record of Tribal relationships with the environment and how those relationships have changed due to colonial land use regimes. In doing so, we highlight how an archaeological research program can be a building point of access to ancestral places, which is a critical step in Tribal-led initiatives of restoring traditional resource management and ecological resilience of plant and animal life on public lands. In addition, we discuss the benefits and limitations of applying ecoarchaeological research toward Tribal environmental stewardship. 1 Introduction Indigenous and collaborative archaeologies have developed as a direct response to critiques expressed by Indigenous peoples. They seek to make the practice of archaeology more equitable, inclusive, and transparent by recognizing the problematic histories that have made the relationships between archaeologists and Indigenous peoples antagonistic and contentious (